Hidradenitis Suppurativa Tunnels: Unveiling a Unique Disease Entity - Nicole Vecin; Nathan C. Balukoff; Marita Yaghi; Tammy Gonzalez; Andrew P. Sawaya; Natasa Strbo; Marjana Tomic-Canic; Hadar Lev-Tov; Irena Pastar (JID Innovations)
Hidradenitis suppurativa tunnel structures lined with epithelium within the dermis are unique features of advanced disease stages that significantly impair patients’ QOL. The presence of hidradenitis suppurativa tunnels is associated with a decreased likelihood of achieving a clinical response, even when receiving biological therapy. The cellular and molecular mechanisms underlying tunnel formation and pathology are only partially understood, which hampers the development of more effective targeted therapies. Tunnels create a unique microenvironment that drives a vicious cycle of hidradenitis suppurativa inflammation, with tunnel keratinocytes exhibiting an activated phenotype characterized by distinct gene expression signatures. In this review, we summarize the current literature and discuss aspects of the pathophysiology of tunnels, including the role of hair follicle epidermal stem cells in tunnel formation, potential role of fibroblast-mediated epithelial–mesenchymal transition, role of dermal papilla fibroblasts, and aberrant proinflammatory repair response contributing to the observed fibrosis and scarring. Finally, tunnel structures are characterized by unique microbial dysbiosis and an overabundance of Gram-negative anaerobes that are not targeted by current therapeutics. In addition to outlining the possible mechanisms of tunnel formation, we provide perspectives on the translation of current knowledge into more effective treatment approaches for patients with hidradenitis suppurativa tunnels.